Accrual Management in the Local Government Of Aceh: An Empirical Evidence - Adnan Adnan; Syukriy Abdullah; Maulana Kamal (Journal of Accounting Research, Organization and Economics, 2023)
Objective –The objective of this study was to examine the factors that influence accruals manipulation in local government. There are 4 (four) factors or variables tested, namely the size of the local government, fiscal capacity, fiscal distress, and the size of the legislature.Design/Methodology –This research uses multiple linear regression analysis with the dependent variable accrual manipulation and four independent variables. The data used is secondary data obtained from financial reports.Results –The results of the analysis conclude that the variable size of local government and size of the legislature have an effect on accrual manipulation in district and city local governments in Aceh, while the other two variables, namely fiscal capacity and fiscal distress, have no effect.Research limitations/implications – This research only examines at the impact of local government size, fiscal capacity, fiscal distress, and legislator size on accrual manipulation in creating local government financial reports in Indonesia and it considers the implications for government financial reports.Novelty/Originality –The novelty in this research is to include the variable fiscal distress as one of the independent variables. Fiscal distress is a problem in fulfilling local government finances (budget), which is reflected in the budget deficit for several years in a row.